New futures for South Asia commerce and connectivity - Subramanyam Raju, A. (Taylor & Francis Group, 2020)
"This book is a comprehensive examination of the society, polity and economy of South Asian countries and their future trajectories. The essays included in the volume present key insights into the geopolitical dynamics of the region. It draws on case studies from the region to discuss how democracy has fared in terms of state-society linkages, transformational possibilities, and globalization and radicalization of politics; It studies possibilities of economic cooperation in South Asia including common currency, regional imbalances and aid, transport connectivity and electricity consumption; It examines the crucial role of SAARC and bilateralism in forging connectivities across the diverse geographies of the region. A major intervention in re-shaping South Asian studies, this book will be a great resource for scholars and researchers of security studies, strategic affairs, international relations, development studies, and politics"--